Qualidade de serviço em uma rede WiFi definida por software - Silva, Fábio de Souza (2022)
Quality of Service (QoS) is a form of management that allows the network user to prioritize data traffic. With the growing demand for wireless connectivity, people started to think about a new form of architecture for these networks, which can be efficient and less costly than traditional architectures and which would enable QoS. Then the software defined network (SDN) architecture emerges and consequently the software defined wireless networks (SDWN). Software defined networks are networks that have an architecture where softwarebased controllers conduct the data traffic. As a SDN, the SDWN also uses controllers to manage data traffic, but with the difference that the network is wireless. One of the characteristics of a SDWN is to facilitate the configuration of QoS on the network through the controller. This paper aims to collect information from a SDWN with QoS through the Mininet-WiFi simulation environment, and analyze these data to report the functioning of this technology.